Re-Locating the Spectator – The Squat Theater’s Use of Media and Space - Zoltán Imre (Symbolon, 2020)
Based on the concepts of intermediality (Balme, Boenisch and Kattenbelt) and heterotopy (Foucault), my paper investigates the special features of the New York-based Squat Theater: their use of media and space. Focusing mostly on their second major, New York-performance, “Andy Warhol’s Last Love” (1978), I would like to analyze how they created a liminal zone (Turner) in-between times and spaces, which re-located the spectators’ position and re-interpreted their function.